Biochemical Differences Between Vitreous Humor and Cerebral Spinal Fluid in a Death From Diabetic Ketoacidosis. (June 2019) - Garland, Jack; Philcox, Winston; Kesha, Kilak; McCarthy, Sinead; Lam, Leo; Palmiere, Cristian; O'Regan, Toni; Stables, Simon; Tse, Rexson
Abstract : Abstract: Biochemical analysis of cerebrospinal fluid (CSF) and vitreous humor (VH) forms an important diagnostic ancillary test at autopsy. Cerebrospinal fluid can be sampled from the ventricular system (VA) and from lumbar puncture (LP), whereas VH can be sampled from the orbits. Biochemical electrolytes seem to vary between VH and CSF collected from different sites, but whether there is any difference in glucose and β-hydroxybutyrate is unclear. We present a case report of a 21-year-old man who died of diabetic ketoacidosis confirmed at autopsy. Ventricular system, LP, and VH were biochemically analyzed and showed that glucose was highest in VH (41 mmol/L) and was 6 and 8 mmol/L higher than CSF in the LP and VA, respectively. β-Hydroxybutyrate was also highest in VH (20 mmol/L) and was 5 and 6 mmol/L higher than LP and VA, respectively. Our findings suggest that postmortem CSF glucose and β-hydroxybutyrate may not truly reflect that of VH and vary between CSF sampling sites.